(untitled) (Global Scientific Review, 2024)
In recent years, uterine extirpation surgery has been performed in the gynecology department. Uterine extirpation occurs in 60% of cases when conservative treatment of uterine myoma has failed. According to research conducted at the Department of Gynecology of the multidisciplinary clinic of the Samarkand State Medical University, in 2022-2023, uterine myoma, which is a component of the extirpation of 150 laparotomy operations, is about 56.2%.